A Study on the Impact of Snapchat Usage Among Youth in Navi Mumbai: Trends, Influences, and Social Behaviour - Garje, Vivek; Mhatre, Rajshree; More, Nilam; Thakur, Gitanjali; Bhosale, Snehal; Dhaigude, Mahesh; Viswasrao, Shubham; Parkar, Safa (International Journal of Engineering and Management Research, 2025)
Snapchat, a leading platform in ephemeral messaging, has significantly transformed the digital habits of young people around the world. In urban areas like Navi Mumbai, it has evolved beyond being just another social media app—emerging as a powerful tool for self-expression, peer bonding, entertainment, and identity construction. This study explores how youth in Navi Mumbai engage with Snapchat and examines the broader social, psychological, and emotional implications of its use. Using a mixed-method approach through surveys and interviews, the research identifies motivations such as privacy concerns, the desire for authenticity, entertainment needs, and peer pressure. Furthermore, it explores the impact of Snapchat on self-image, social interactions, attention span, and emotional well-being. The research highlights key concerns, including digital dependency, reduced face-to-face communication, and the pursuit of online validation. Practical recommendations are offered for educators, parents, and policymakers to promote healthier, more balanced digital practices among youth.